Surveillance of Global Corruption by Transparency International: Construction of a ‘Corrupt’ South and ‘Clean’ North Discourse (Philosophy and Progress, 2022)
This study looks at how discourses of corruption in Bangladesh are discursively constructed within the official documents of Transparency International (TI), a non-profit organization that monitors corruption worldwide. It explores how an orientalist notion regarding Bangladesh is appropriated in neoliberal global discourse through TI’s corruption surveillance process. A postcolonial analysis of TI’s publications demonstrates a symbiotic relation between orientalism and neoliberalism. TI sets up a binary of ‘corrupt’ global South vs. ‘clean’ global North, reinforcing the uneven power relations between nation-states that can be seen as a neocolonial move for maintaining Western hegemony and enabling neoliberal ideology over non-Western territories.Philosophy and Progress, Vol#67-68; No#1-2; Jan-Dec 2020 P 49-76